2021
DOI: 10.3889/oamjms.2021.6603
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Collaborative Model between the Role of Husbands and Healthcare Workers on Mother’s Behavior in Giving Exclusive Breastfeeding

Abstract: BACKGROUND: Considering the importance of giving exclusive breast milk (ASI) for the growth and development of children, collaborative support between health workers and husbands is very important. Support from husbands allows mothers to carry out breastfeeding process easier, so that the mothers’ mental condition will be stable and not stressful, and they will not feel exhausted. As a result, the mothers can provide the best breast milk. AIM: The aim of this study is to analyze the influence of a collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Previous studies revealed that husbands who understood their role in supporting breastfeeding mothers during postnatal care, such as providing verbal encouragement and sharing household duties, can increase exclusive breastfeeding duration. 27 This support also increases interpersonal influences, directly impacting breastfeeding behavior, which aligns with the conceptual framework.…”
Section: Pacific Rim Int J Nurs Res • July-september 2024supporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies revealed that husbands who understood their role in supporting breastfeeding mothers during postnatal care, such as providing verbal encouragement and sharing household duties, can increase exclusive breastfeeding duration. 27 This support also increases interpersonal influences, directly impacting breastfeeding behavior, which aligns with the conceptual framework.…”
Section: Pacific Rim Int J Nurs Res • July-september 2024supporting
confidence: 52%
“…24,25 Additionally, family support has also been reported to promote the maintenance of breast milk production. 26,27 Therefore, healthcare providers and the family are significant sources of social support that directly affect breastfeeding intention.…”
Section: Conceptual Framework and Review Of Literaturementioning
confidence: 99%